Genome damage in children with classical Ehlers-Danlos syndrome - An in vivo and in vitro study - Aghajanyan, Anna; Fucic, Aleksandra; Tskhovrebova, Leila; Gigani, Olga; Konjevoda, Pasko (European journal of medical genetics, 2019)
Ehlers-Danlos syndrome (EDS) is a heritable connective tissue disorder characterized by skin hyperextensibility, abnormal wound healing, and joint hypermobility with prevalence 1:20 000. Its incidence is probably underestimated due to unknown number of subjects having mild symptoms who may have never been diagnosed through entire life time. Classical EDS is characterized by pathogenic variants of genes encoding type V collagen. The biological effects and health risks of patients with EDS exposure to low doses of ionizing radiation is poorly understood. The aim of this study was to investigate biological effect of low doses of ionizing radiation in children with EDS. Background values of chromosome aberrations in children suffering from classical EDS were determined and compared with control subjects. The in vitro experiment was performed by γ-irradiation of blood lymphocytes from EDS patients and healthy subjects at low doses (0.1, 0.2 and 0.3 Gy). Results show a significant increase level of spontaneous and radiation-induced chromosomal aberrations in children suffering from EDS in comparison with the control subjects (p < 0.05). In conclusion, children with EDS express higher background chromosome aberration frequency and increased radiosensitivity. These findings suggest specific susceptibility of EDS patients and importance of future investigation on risks of diagnostics and therapy which include radiation and genotoxic agents.